Methods of choosing the best methods of building a dynamic visualization environment - Бородін, В.А.; Креденцар, С.М. (Proceedings of National Aviation University (archive), 2009)
In work is offered the methods of the choice of the most optimum combination of the methods which provides the building of the visual image of the dynamic scenes on the displays of real-time ANGS, which defines the optimal percent of the use for each of m software programs, that are in complex, n methods, optimizing velocity of the image of the visual image. The calculation of the ratio is carried out using the details of this problem to the linear programming problem. In work is offered the calculation of the optimum methods for building a visual image of a dynamic scenes for a specific task.